Asylum seekers and inequalities in healthcare: a mixed-method research in Emilia-Romagna region. (30th September 2020) - Gherardi, G; Mammana, L; Quargnolo, M; Bodini, C; Damosto, D; Florescu, C; Fantini, M P
Abstract: Background: In the past few years more than 30, 000 asylum seekers arrived in Emilia-Romagna region. Guidelines were developed to screen the newly arrived, mainly focused on communicable diseases (CDs). However, asylum seekers who are out of the institutional reception system do not have access to such screenings. In order to assess the implementation and reach of these guidelines with respect to the target population, in 2019 a mixed-method survey was carried out. Methods: A questionnaire with 35 closed and 11 open questions, based on a synthesis of the regional and national guidelines, was carried out with referents of the regional clinics that provide healthcare to asylum seekers. The collected questionnaires were processed through descriptive statistical analysis for the closed questions and text analysis for the open questions. Results: Questionnaires were collected from 14 clinics. All clinics provide first visit and screening for CDs upon arrival, following the regional guidelines. However, enrolment in the national healthcare system was found to be delayed for periods of up to 6 months, resulting in discontinuity of care. Administrative and cultural barriers in accessing health and social services were repeatedly reported, the latter often linked to lack of cultural mediation services. Financial barriers were also reported, particularly with respect to dental care and pharmaceuticals. Results also show that asylum seekers within the institutional reception system can more easily overcome the reported barriers compared to those out of the system. Such inequality in accessing healthcare is reported also for the TB screening process. Conclusions: Even if access to healthcare for asylum seekers is regulated by norms and guidelines, barriers are consistently reported. Moreover, asylum seekers within or outside the reception system face different barriers in accessing healthcare services. Such local evidence can be very relevant to inform actions that improve health equity. Key messages: Even if access to healthcare for asylum seekers is regulated by law, barriers are consistently reported and impact disproportionately on those who are out of the institutional reception system. A mixed-method approach that generates local evidence on the barriers that asylum seekers face in accessing healthcare and on their causes is key to inform actions that improve health equity.